2021
DOI: 10.3390/ani11051222
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Starch Concentration Affects Dairy Sheep and Goat Performances Differently during Mid-Lactation

Abstract: Evolution of milk production, body reserves and blood metabolites and their relationships with dietary carbohydrates were compared in 30 Sarda dairy ewes and 26 Saanen dairy goats in mid-lactation. From 92 to 152 ± 11 days in milk (DIM), each species was allocated to two dietary treatments: high-starch (HS: 20.0% starch, on DM basis) and low-starch (LS: 7.8% starch, on DM basis) diets. In mid-lactating goats, the HS diet increased fat-corrected milk yield (FCM (3.5%); 2.65 vs. 2.53 kg/d; p = 0.019) and daily m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…Ewes receiving the diet with grain legumes were able to utilize energy and protein supply towards meeting the demands for maintenance and milk production in an equally efficient way with those receiving soybean. Grain legumes have a high starch content and previous research has suggested that such diets could potentially favour fat deposition over milk production [56]. The latter was not corroborated from results in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Ewes receiving the diet with grain legumes were able to utilize energy and protein supply towards meeting the demands for maintenance and milk production in an equally efficient way with those receiving soybean. Grain legumes have a high starch content and previous research has suggested that such diets could potentially favour fat deposition over milk production [56]. The latter was not corroborated from results in our study.…”
Section: Discussioncontrasting
confidence: 99%